Protein engineering for metabolic engineering: current and next-generation tools - Marcheschi, Ryan J. (2013)
Protein engineering in the context of metabolic engineering is increasingly important to the field of industrial biotechnology. As the demand for biologically-produced food, fuels, chemicals, food additives, and pharmaceuticals continues to grow, the ability to design and modify proteins to accomplish new functions will be required to meet the high productivity demands for the metabolism of engineered organisms. This article reviews advances of selecting, modeling, and engineering proteins to improve or alter their activity. Some of the methods have only recently been developed for general use and are just beginning to find greater application in the metabolic engineering community. We also discuss methods of generating random and targeted diversity in proteins to generate mutant libraries for analysis. Recent uses of these techniques to alter cofactor use, produce non-natural amino acids, alcohols, and carboxylic acids, and alter organism phenotypes are presented and discussed as examples of the successful engineering of proteins for metabolic engineering purposes.